Behavior of eccentrically loaded circular tubed steel-reinforced concrete short columns using high-strength concrete. (March 2022) - Wang, Xuanding; Liu, Jiepeng; Li, Xiang; Chen, Y. Frank
Abstract: The tubed steel reinforced-concrete (TSRC) column is a compression member composed of a thin-walled steel tube filled with the structural steel shape-reinforced concrete, in which the steel tube is disconnected at the beam-column connections while providing a strong lateral restraint to the core concrete. To access the structural behavior of circular TSRC (referred as "CTRSC") column using the HSC, a total of 11 short column specimens with the cubic concrete strength of 81.4 MPa were tested under the eccentric compression. The load eccentricity and the diameter-to-thickness ratio of steel tubes were considered as the key parameters; and their influences on the failure mode, load-bearing capacity, and deformation characteristics were investigated. The experimental results indicate that the failure sections of the test specimens strongly depend on the load eccentricity and the use of steel tube improves the ductility of HSC and ensures the composite action between the concrete and the structural steel shape. A simplified calculation method for the resistance of eccentrically loaded CTSRC columns is proposed, which gives satisfactory predictions when compared with the test results and the theoretical model.